Patience and Tawakal in Nursing Practice at Psychiatric Hospitals - Dalimunthe, Hazra Ria Habibah; Faishal, Muhammad (JIE (Journal of Islamic Education), 2024)
This study aims to illustrate that being a nurse in a psychiatric hospital requires patience and a high level of tawakal. With patience and tawakal, nurses can perform their responsibilities optimally. This research employs a qualitative case study approach. Data collection techniques include observation (directly reviewing the research location) and interviews (conducting direct question-and-answer sessions with nurses in the rehabilitation section), supported by accurate evidence in the form of documentation. The results of this study indicate that nurses at the Special UPTD of Prof. Dr Muhammad Ildrem Psychiatric Hospital, North Sumatra Province, successfully embody the concepts of patience and tawakal when dealing with patients. Moreover, patience and tawakal are exhibited in interactions with patients, colleagues, and patient's families. Additionally, these nurses provide exemplary health services that align with religious teachings. The implications of these practices are far-reaching, improving patient care, enhancing nurse-patient interactions, fostering teamwork, and supporting nurses' psychological resilience. Integrating Sufism principles into nursing practice offers a unique and practical approach to managing the complexities of psychiatric care, ultimately contributing to better health outcomes and a more supportive work environment for nurses.